PEMBENAHAN DUSUN SEBAGAI BENTUK ANTUSIAS MASYARAKAT DALAM MENYAMBUT HARI KEMERDEKAAN INDONESI 17 AGUSTUS: Village Improvement As A Form Of Community Enthusiasm In Welcoming Indonesian Independence Day, August 17 - Aminullah, Aminullah; Titawati, Titin; Ardika, Gede Tusan; Ramli, Ramli; Loilewen, Aline Febriany; Nopiari, Ida Ayu; Jaya, Nenet Natasudian; Subrata, I Gusti Made (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
This Community Service (PKM) aims to improve the hamlet as a form of community enthusiasm in welcoming Indonesian Independence Day on August 17th in Kongok Hamlet, Meninting Village, West Lombok Regency. The method for realizing community service activities is through: 1) Formation of the Committee for the Commemoration of the Indonesian Independence Day of Kongok Hamlet consisting of the Hamlet Head and RT/RW of Kongok Hamlet, Community Leaders, Lecturers and Students. 2) Implementation of community service for improving the hamlet and preparing for other 17th activities. The results of the community service program to improve the hamlet as a form of community enthusiasm in welcoming Indonesian Independence Day on August 17th in Kongok Hamlet, Meninting Village, Batu Layar District, West Lombok Regency were carried out through collaboration between lecturers, Community Service Program students, the hamlet government, and the local community. The hamlet improvement included painting the hamlet's perimeter walls, painting and improving the hamlet gate, and preparing and holding 17th August competitions to improve and foster community unity, such as tug-of-war, cracker-eating competitions, and competitions held at the village and sub-district levels. The series of activities carried out by the community were always busy and the level of community participation was high, so it can be said that the residents of Kongok Hamlet were very enthusiastic about the hamlet improvement in commemoration of the Indonesian Independence Day on August 17th